Analysing Osteotomy Drilling Speed on Cortical Bone on Implant Stability and Bone Healing - Basannavar, Amit Ashok; Sahoo, Sushil Kumar; Bera, Olivia; Kamila, Pranati; Nayak, Anisha; Verma, Praveen (Journal of Neonatal Surgery, 2025)
Background: Osteotomy drilling speed plays a critical role in dental implantology, influencing both primary implant stability and subsequent bone healing. Excessive drilling speeds may generate thermal damage, compromising osseointegration, whereas lower speeds may enhance bone preservation. This study aims to evaluate the impact of different drilling speeds on cortical bone during implant site preparation and assess their effects on implant stability and bone healing outcomes. Materials and Methods: A total of 30 implant sites were prepared in bovine cortical bone samples, divided equally into three groups based on drilling speeds: Group A (800 rpm), Group B (1200 rpm), and Group C (1600 rpm). Standardized saline irrigation was applied across all groups. Primary implant stability was measured using the Implant Stability Quotient (ISQ) immediately after placement. Histological analysis was conducted after 6 weeks to assess bone healing and new bone formation around the implants. Results: Group A (800 rpm) demonstrated the highest mean ISQ value of 75 ± 2, followed by Group B (1200 rpm) with 70 ± 3, and Group C (1600 rpm) with 65 ± 4. Histological evaluation revealed greater new bone formation in Group A (68% bone-to-implant contact) compared to Group B (60%) and Group C (52%). Higher drilling speeds correlated with increased signs of thermal osteonecrosis and delayed bone remodeling. Conclusion: Lower osteotomy drilling speeds significantly enhance primary implant stability and promote superior bone healing by minimizing thermal damage to cortical bone. Optimal drilling protocols emphasizing reduced speeds with adequate irrigation may improve clinical outcomes in dental implant procedures.